On realizing autonomous transport services in multi story buildings with doors and elevators - Schulze, Paul Robert; Müller, Steffen; Müller, Tristan; Gross, Horst-Michael (Frontiers in Robotics and AI, 2025)
Mobile service robots for transportation tasks are usually restricted to a barrier-free environment where they can navigate freely. To enable the use of such assistive robots in existing buildings, the robot should be able to overcome closed doors independently and operate elevators with the interface designed for humans while being polite to passers-by. The integration of these required capabilities in an autonomous mobile service robot is explained using the example of a SCITOS G5 robot equipped with differential drive and a Kinova Gen II arm with 7 DoF. This robot also defines the framework conditions with certain limitations in terms of maneuverability and perceptual abilities. Results of field tests with that robot in an elderly care facility as well as in a university office building are shown, where it performed transportation and messaging tasks. We also report on the success rates achieved and highlight the main problems we have encountered and dicsuss open issues.